Keterkaitan antara Faktor Sosiodemografi dengan Sikap Siswa terhadap Lingkungan - Yusup, Febrianawati (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2022)
Environmental damage that occurs must be repaired. Only individuals with environmental literacy are able to resolve environmental problems. Environmental Education (EE) is important way to educate people about environmental issues. One of the affective learning outcomes of EE is the student environmental attitude. EE,besides standing alone, can also be integrated with biology. However, students’ environmental attitude formed from many factors, not only from EE and biology learning. Research on students’ environmental education influencing factor, involve 192 high schools students majoring in Mathematics and Science, uses astudent biodata to explore students sociodemographic factors and student’s environmental attitude quesioner to explore students’ environmental attitude. The results showed that only gender that influences students’ environmental attitude, while duration of EE and biology learning, as well as parent’s educational background do not influence students’ environmental attitude. Learning to improve students’ environmental attitude needs to pay attention to gender.